2022
DOI: 10.1097/mcc.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus pandemic on sedation in critical care: volatile anesthetics in the ICU

Abstract: Purpose of review To reflect on the impact of the coronavirus pandemic on sedation for mechanically ventilated patients. Recent findings Shortages of intravenous sedatives during coronavirus pandemic renewed interest in using widely available inhaled anaesthetics for sedation of critically ill patients. Universally used for surgical anaesthesia, inhaled anaesthetics may offer therapeutic advantages in patients with acute lung injury with good sedation profiles, rapid cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Landoni et al's meta-analysis found a reduced need for intravenous sedatives and opioids when using inhalation sedation [58]. Alongside sedation, inhaled anesthetics may provide other clinical benefits-bronchodilatation, reduced inflammation, improved gas exchange, and facilitated awakening [63,64].…”
Section: Prevention and Treatment Of P-silimentioning
confidence: 99%
“…Landoni et al's meta-analysis found a reduced need for intravenous sedatives and opioids when using inhalation sedation [58]. Alongside sedation, inhaled anesthetics may provide other clinical benefits-bronchodilatation, reduced inflammation, improved gas exchange, and facilitated awakening [63,64].…”
Section: Prevention and Treatment Of P-silimentioning
confidence: 99%